NOT JUST AN ENTITLEMENT: A JOB PROFILE-BASED GOVERNANCE STRATEGY FOR FLEXIBLE WORKING ARRANGEMENT AT BPS-STATISTICS INDONESIA - Eka Widi Handayani; Mala Sondang Silitonga (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The implementation of Flexible Working Arrangements (FWA) in public sector organizations requires governance mechanisms that balance work flexibility with accountability and service quality. However, existing studies have predominantly focused on the effects of FWA on individual outcomes, while limited attention has been given to governance strategies that accommodate heterogeneous job characteristics. This study aims to analyze the factors influencing FWA implementation and to develop a job profile-based governance strategy in Statistics Indonesia (Central Statistics Agency). A qualitative case study approach was employed using in-depth interviews, document analysis, and observation. The data were analyzed through the interactive model of Miles, Huberman, and Saldaña. The findings indicate that effective FWA implementation depends on the integration of regulatory support, leadership, digital readiness, work coordination requirements, and job profile suitability. The study further demonstrates that a uniform FWA policy is unlikely to achieve optimal outcomes because different job profiles require different degrees of work flexibility. Based on these findings, the study proposes a job profile-based governance strategy that integrates adaptive regulations, job-oriented work arrangements, digital monitoring systems, and output-based performance evaluation. This study contributes to the public administration literature by reframing FWA as a contingency-based governance approach, where implementation is designed according to job characteristics rather than standardized work flexibility, thus promoting more effective, accountable, and sustainable public sector governance.